Molecular evidence of Bartonella DNA in ixodid ticks in Czechia - Hercík, K; Hásová, V; Janecek, J; Branny, P (Folia microbiologica, 2007)
We report the development of a novel method for detection of Bartonella DNA in ixodid ticks. The assay is based on a specific amplification of a part of 16S rRNA gene and 16S-23S rRNA intergenic spacer region of Bartonella sp. by nested PCR and Southern blot hybridization with specific DNA probe; the method is highly sensitive and specific. The screening of 327 unfed ticks collected in different urban and suburban areas of Czechia in 2003-2005 revealed the presence of Bartonella DNA in four Ixodes ricinus individuals (1.2%), two males, one female and one nymph.
Keywords: polymerázová řetězová reakce; RNA ribozomální 16S; Blotting, Southern; RNA ribozomální 23S; lidé; intergenová DNA; Southernův blotting; oligonukleotidové sondy; ribozomální DNA; Bartonella; senzitivita a specificita; Female; DNA bakterií; Sensitivity and Specificity; Oligonucleotide Probes; Humans; Polymerase Chain Reaction; RNA, Ribosomal, 23S; RNA, Ribosomal, 16S; DNA, Bacterial; Česká republika; DNA, Ribosomal; mužské pohlaví; zvířata; Ixodidae; DNA, Intergenic; Czech Republic; ženské pohlaví; Animals; Male